Budaya Majlas dalam Komunitas Keturunan Arab di Ampenan - Baiq Raudatussolihah; Ali Fathurrahman; Abdurrahman Alhabsyi (LP2M STIT Palapa Nusantara, 2022)
Starting from the construction of darun nadwah as a meeting place for discusses the problems experienced by the tribes of the Qureish tribe to find a solution together until the arrival of Islam as a unifying religion. Human discussion is a habit that has become a routine for the Arabs. Likewise, when Islam is present and spread throughout the world, including Indonesia. This habit becomes very attached and becomes a culture for people of Indonesian Arab descent, especially Ampenan Arab descent who, although the name changed to majlas but the essence is the same as the association – the association created by his predecessors. This study uses a qualitative descriptive method with a approach ethnography and discuss about the majlas culture in the Arab community in Ampenan and find out if this custom is the same as the gathering - past gatherings, as well as whether the majlas gave birth to good outputs related to the economy education and social community.